The Effect of Digital Banking Adoption, Trust in Fintech, Perceived Security, and Customer Satisfaction on Financial Inclusion in Indonesian Banking - Ridwan, Mohammad; Puspitasari, Ria; Winarsih, Tri; Wangsih, Ingkak Chintya; Sudarmanto, Eko (Westscience Press, 2025)
This study investigates the impact of Digital Banking Adoption, Trust in Fintech, Perceived Security, and Customer Satisfaction on Financial Inclusion in Indonesian banking. Employing a quantitative approach, data were collected from 110 respondents using a Likert scale (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The findings reveal that all four variables significantly and positively influence financial inclusion, with Digital Banking Adoption exerting the strongest impact. The model explains 68% of the variance in Financial Inclusion, underscoring the importance of digital transformation, trust-building, robust security, and customer satisfaction in enhancing financial accessibility. These results provide valuable insights for policymakers and financial institutions to develop targeted strategies that foster financial inclusion in Indonesia.